L’ermetismo e Firenze (Moderna/Comparata, 2016)
This is the second of the two volumes dedicated to Hermeticism and Florence published by Firenze University Press (the first one entitled Critici, traduttori, maestri, modelli can be purchased separately). Between 1930 and 1945, a group of young people started one of the most vibrant literary seasons of the 20th century in Florence. Many of them recognized themselves in a common narrative marked by a shared imagination, and in the silent dissent from the rhetoric of the regime, which was contrasted by the radicalism of the ethical request and by the deep bond with the Jewish-Christian, romantic and -symbolist roots of the European civilization. One hundred years after the birth of its protagonists (Mario Luzi, Piero Bigongiari, Alessandro Parronchi, Vittorio Bodini), there are still doubts surrounding Hermeticism, its birth and its distinctive features. Searching for how it changed, why it was surrounded by prejudices and aversion (as done by the two essential volumes collecting the documents of a memorable conference in which Anna Dolfi involved scholars from all over the world), leads to draw a portrait of the Hermetic authors, its critics (Bo, Macrí), its friends (the generational companion Vittorio Sereni), admirers and/or detractors, and to outline the boundaries of a complex chapter of Italian history which began with Fascism and recently ended with the fall of ideologies. Together with its 'players', Florence is in a prominent position, a city which, for a few decades, was exposed to the greatness of the past by a new passion, made of culture, creativity and intelligence.